3
$\begingroup$

So, not sure if I'm really dumb and not getting something obvious or if there is more complexity here...Let's do 2 objects first. Say C.O.M. is x°.

Then $x° = \dfrac{x_1M_1 +x_2M_2}{M_1+M_2} $

I get the "idea" of this formula–you are in a sense averaging the value of the masses. But is there some blatantly obvious reason for why this is true? It can easily be derived from:

$(x°-x_1)M_1 = (x_2-x°)M_2$

but I don't see why the initial statement ($x° = \dfrac{x_1M_1 +x_2M_2}{M_1+M_2} $) is a priori true. Is there a geometric intuition?

If we are doing a continuous non-constant function:

$\int_{a}^{x°}f(x)(x°-x)dx= \int_{x°}^{b}f(x)(x-x°)dx $

It can be derived that this is equal (if I did it right) to $\dfrac{\int_{a}^{b}xf(x)dx}{\int_{a}^{b}f(x)dx} $

But again, is there a more obvious geometric intuition? Thanks

$\endgroup$
  • 2
    $\begingroup$ There is nothing to derive: it is a definition. As you say, the intuition the definition is trying to capture is that you are taking a weighted average of positions (not masses), where the weights correspond to mass. $\endgroup$ – symplectomorphic Mar 15 '17 at 23:30
  • 1
    $\begingroup$ To the extent there is intuition for the definition, that is a Physics question, not a math one. $\endgroup$ – Paul Mar 15 '17 at 23:52
2
$\begingroup$

From the point of view of mathematics, there is no further explanation. The formula $$(x°-x_1)M_1 = (x_2-x°)M_2$$ has to be considered as an axiom. The motivation comes from physics, and is related to the following image of masses balancing each other:

enter image description here

$\endgroup$
  • $\begingroup$ No I understand the $(x°-x_1)M_1$ part...but can you explain the intuition of the weighted average? (see edit) $\endgroup$ – swedishfished Mar 15 '17 at 23:43
  • $\begingroup$ I am sorry but I don't understand the comment. I saw the edit but I don't see the difference. Please, please, explain in the question marked as EDIT. $\endgroup$ – zoli Mar 15 '17 at 23:56
1
$\begingroup$

Notice the definition of center of mass $x_c$ for two particles rearranges to

$$x_c = \Big(\frac{m_1}{m_1+m_2}\Big)x_1+\Big(\frac{m_2}{m_1+m_2}\Big)x_2$$

Let's call the ratio $(\frac{m_1}{m_1+m_2})$ "$W_1$". It can can be interpreted as the percentage of mass that object 1 contributes to the system, generally $(\frac{mass of object 1}{total mass})$. To convert to units of percentage simply multiply the resulting decimal by 100%. Notice that $W_1 \leq 1$, that is object 1 (any object) cannot contribute more that 100% of the mass of the system.

In general a weighted average (arithmetic mean) $x_{av}$ of $n$ components is

$$x_{av} = w_1x_1 + w_2x_2 + ... + w_nx_n = \sum_{i=1}^{n} w_ix_i$$

where $w_i$ is the weight (in the statistical sense) of component $x_i$. For convenience we often wish for the weight factors to be normalized, that is,

$$\sum_{i=1}^{n} W_i = 1$$

Notice here I wrote $W_i$, the normalized weight factors, instead of $w_i$, which are not necessarily normalized.

For your physics application of this math, the mass $m_i$ of object $i$ corresponds to the "crude" weight factor $w_i$. To normalize weight factors (so that none is greater than 100%), we divide the crude factor by the total weight of all components:

$$W_i = \frac{w_i}{\sum_{i=1}^{n} w_i}$$

or, for us, the object mass by the total mass of the system:

$$W_i = \frac{m_i}{\sum_{i=1}^{n} m_i} = \frac{m_i}{M} $$

(where "$M$" is a common abbreviation for the total system mass that is, $M = \sum_{i=1}^{n} m_i$.) This is why our weight factors for calculating center of mass consist of the mass of the object divided by the total mass of the system. For two objects ($n=2$), the weight factor $W_i$ for object $i$ is of course

$$W_i = \frac{m_i}{\sum_{i=1}^{2} m_i} = \frac{m_i}{m_1+m_2} $$

Thus,

$$x_c = \Big(\frac{m_1}{m_1+m_2}\Big)x_1+\Big(\frac{m_2}{m_1+m_2}\Big)x_2 \\ = \sum_{i=1}^{2} \Big(\frac{m_i}{m_1+m_2}\Big) x_i \\ = \frac{\sum_{i=1}^{2} m_ix_i}{\sum_{i=1}^{2} m_i} \\ = \frac{1}{M} \sum_{i=1}^{2}x_im_i$$

I've written a few forms of $x_c$ above so you can mull over how this expression is constructed. For the general center of mass of a system of $n$ objects, simply replace $2$ with $n$ in the final expression.

Let's explicitly juxtapose our center of mass formula with the weighted average formula to drive the point home:

$$x_{av} = \sum_{i=1}^{n} W_ix_i \\ \\ x_c= \sum_{i=1}^{n} \Big(\frac{m_i}{M}\Big) x_i$$

Thus, the center of mass is the weighted average of position with respect to mass. $$\\ \\$$ P.S. If the system has a continuous distribution of mass rather than $n$ discrete chunks (as for any real object that is not being approximated as a dimensionless point particle), instead of

$$x_c = \frac{1}{M} \sum_{i=1}^{n}x_im_i$$

We can use

$$x_c = \frac{1}{M} \int xdm$$

which arises when we take the limit as $n \to \infty$. (Note this form is not the most practical to calculate so we usually make the substitution $dm = \rho dV$ where $\rho$ is the density of the object, which may vary with position.)

$\endgroup$
  • 1
    $\begingroup$ This answer gets to the heart of the misconception in the question: the formula is a kind of average of the positions, not an average of the masses. $\endgroup$ – David K Mar 16 '17 at 13:25

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.